2014
DOI: 10.3892/mmr.2014.2928
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mild induced hypothermia on hippocampal connexin 43 and glutamate transporter 1 expression following traumatic brain injury in rats

Abstract: Traumatic brain injury (TBI) is a common cause of worldwide disability and mortality. Currently, the incidence and prevalence of TBI is markedly increasing and an effective therapy is lacking. Therapeutic hypothermia (32‑35˚C) has been reported to reduce intracranial pressure and induce putative neuroprotective effects. However, the underlying molecular mechanisms remain to be elucidated. The aim of the present study was to investigate the effects of mild induced hypothermia (MIH) on the expression of connexin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Studies in postmortem human brain tissue derived from TBI patients have demonstrated decreased expression of EAAT1 and 2 in astrocytes and microglia (Ikematsu et al, 2002;van Landeghem et al, 2006;Beschorner et al, 2007), which could contribute to impaired glutamate buffering. Mouse models of TBI have corroborated these observations (Rao et al, 1998;Li et al, 2015), and it could be reverted by treatment with ceftriaxone, an antibiotic that upregulates GLT-1 (Goodrich et al, 2013). In this regard, the increase expression in GLT-1 by ceftriaxone reduce post-traumatic seizures and gliosis (Goodrich et al, 2013).…”
Section: Traumatic Brain Injury and The Astrocytic Responsementioning
confidence: 74%
“…Studies in postmortem human brain tissue derived from TBI patients have demonstrated decreased expression of EAAT1 and 2 in astrocytes and microglia (Ikematsu et al, 2002;van Landeghem et al, 2006;Beschorner et al, 2007), which could contribute to impaired glutamate buffering. Mouse models of TBI have corroborated these observations (Rao et al, 1998;Li et al, 2015), and it could be reverted by treatment with ceftriaxone, an antibiotic that upregulates GLT-1 (Goodrich et al, 2013). In this regard, the increase expression in GLT-1 by ceftriaxone reduce post-traumatic seizures and gliosis (Goodrich et al, 2013).…”
Section: Traumatic Brain Injury and The Astrocytic Responsementioning
confidence: 74%
“…Astrogliosis is categorized by increased GFAP + and vimentin across TBI models, yet away from the glial scar, the morphological significance of this gliosis is temporally and spatially dynamic [ 14 ]. They contribute to brain edema after injury [ 150 152 ], and contain decreased expression of GLT-1, GLAST and EAAT1/2, evidencing their role in TBI-induced glutamate dysregulation [ 153 156 ]. They also contribute directly to immune responses through DAMP/TLRs signaling as well as proinflammatory cytokine and chronic complement production after TBI [ 157 160 ].…”
Section: Neuroinflammation In Tbimentioning
confidence: 99%
“…To address this issue, experimental and clinical investigations have clarified an extensive list of injury processes that are sensitive to brain temperature variations during or following injury (Atkins et al, 2007; Chatzipanteli et al, 1999; Chatzipanteli et al, 2000; Polderman, 2009; Suzuki et al, 2003; Vitarbo et al, 2004). Previous review articles have thoroughly discussed these temperature sensitive processes that include excitotoxicity, free radical generation, programmed cell death and neuroinflammation (Dietrich, 1992; Dietrich et al, 2009; Dietrich and Bramlett, 2010; Han et al, 2015; Li et al, 2015; Lotocki et al, 2011; Truettner et al, 2005; Yenari and Han, 2012; Yenari and Han, 2013). In one early study using in vivo microdialysis, Globus and colleagues for example reported that extracellular levels of glutamate and indicators of free radical formation were dramatically reduced with hypothermia compared to normothermia (Globus et al, 1995).…”
Section: Mechanisms Underlying Temperature Effectsmentioning
confidence: 99%